On the Endogenous Choice of Bertrand Vs. Cournot Equilibrium in a Duopoly - Flavio Delbono; Marco Mariotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
We try to endogenise the choice between Bertrand Equilibrium (BE) and Cournot Equilibrium (CE) in simple duopoly models. The two distinctive features of this paper as compared to the related literature are the following. First, we take the concepts of BE an CE as fundamental and restict players' choices to these two equilibria. Second, we adopt a forward induction criterion to shrink the Nash equilibrium set of our games. Our findings suggest the BE seems more vulnerable than the CE whenever forward induction is taken seriously.
Keywords: 330